Educational Technology / Opvoedkundige Tegnologie: Instructional Media - Parkins, N.C. (Scientia Militaria - South African Journal of Military Studies, 2012)
The universal question so often asked by instructors is how does one choose which medium to use for different parts of a course. The questioner usually expects to be referred to a beautifully constructed algorithm or a carefully balanced analysis of pedagogical factors which will lead to a best choice. No such things exist. Instead choice of media is still very much controlled by logistical financial and internal political factors. 'Gut feeling' is still an important means of selecting media.